## Simplifying (7x + 2)^2

The expression (7x + 2)^2 represents the square of a binomial. To simplify this, we need to expand the expression using the **FOIL method** or the **square of a binomial pattern**.

### Expanding with FOIL

**FOIL** stands for **First, Outer, Inner, Last**. This method helps us multiply two binomials by considering each term of the first binomial with each term of the second binomial.

**First:**(7x) * (7x) = 49x²**Outer:**(7x) * (2) = 14x**Inner:**(2) * (7x) = 14x**Last:**(2) * (2) = 4

Now, we add all the terms together: 49x² + 14x + 14x + 4

Finally, combine like terms to get the simplified expression: **49x² + 28x + 4**

### Using the Square of a Binomial Pattern

The square of a binomial pattern states: (a + b)² = a² + 2ab + b²

In our case, a = 7x and b = 2. Applying the pattern, we get:

(7x + 2)² = (7x)² + 2(7x)(2) + (2)²

Simplifying the expression: 49x² + 28x + 4

### Conclusion

Therefore, the simplified form of (7x + 2)² is **49x² + 28x + 4**. Both the FOIL method and the square of a binomial pattern lead to the same result. Choose the method that feels more comfortable for you.